1988
DOI: 10.2307/2403842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutrient Enrichment on the Auchenorrhyncha (Homoptera) in Contrasting Grassland Communities

Abstract: Auchenorrhyncha were sampled from control, fertilizer-and sludge-treated plots within agricultural and fourth-year old-field communities. (2) Nutrient enrichment significantly increased net primary productivity in both plant communities. (3) Functional plant community properties (e.g. net primary production) were more robust indicators of nutrient enrichment than were structural properties (e.g. plant species diversity). (4) Nutrient-enriched plots generally exhibited higher Auchenorrhyncha population densitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 47 publications
2
35
1
Order By: Relevance
“…Herbivore and detritivore biomass also increased in some fertilised blocks, but this effect was weak and variable (Table 2), consistent with a related study that showed smaller individuals dominate the response to nutrient enrichment (Gruner, 2004b). Responses of community species richness or diversity in other studies have been more variable and equivocal than abundances (Hurd & Wolf, 1974;Kirchner, 1977;Sedlacek et al, 1988;Haddad et al, 2000). Discrepancies in the qualitative responses of diversity across systems may be biologically based and system specific, or might vary according to differences in spatial scale (Whittaker & Heegaard, 2003), trophic or taxonomic focus (Haddad et al, 2000), diversity metric or standardisations employed (McCabe & Gotelli, 2000), or experimental time frame (Haddad et al, 2000).…”
Section: Community Responses To Fertilisationsupporting
confidence: 86%
“…Herbivore and detritivore biomass also increased in some fertilised blocks, but this effect was weak and variable (Table 2), consistent with a related study that showed smaller individuals dominate the response to nutrient enrichment (Gruner, 2004b). Responses of community species richness or diversity in other studies have been more variable and equivocal than abundances (Hurd & Wolf, 1974;Kirchner, 1977;Sedlacek et al, 1988;Haddad et al, 2000). Discrepancies in the qualitative responses of diversity across systems may be biologically based and system specific, or might vary according to differences in spatial scale (Whittaker & Heegaard, 2003), trophic or taxonomic focus (Haddad et al, 2000), diversity metric or standardisations employed (McCabe & Gotelli, 2000), or experimental time frame (Haddad et al, 2000).…”
Section: Community Responses To Fertilisationsupporting
confidence: 86%
“…This reduction in species richness may have an impact on specialized herbivores, as has been seen in diversity experiments (Haddad et al 2009, Scherber et al 2010. However, productivity gains in structural complexity and productivity may increase invertebrate species richness and the net effect of fertilization of the species richness on higher trophic levels can be both positive and negative (Sedlacek et al 1988, Haddad et al 2000. In our grasslands, fertilization is strongly correlated with higher mowing frequencies; this disturbance and removal of additional biomass results in a negative overall effect on the diversity of both plant and primary consumer taxa.…”
Section: Discussionmentioning
confidence: 90%
“…However, the estimates of species richness from individual-based rarefaction did not increase with fertilization for any trophic group. Numerous studies have examined the diversity of herbivorous or other arthropods in response to fertilization, but generalizations have been elusive (e.g., Hurd and Wolf 1974;Kirchner 1977;Kajak 1981;Vince et al 1981;Prestidge 1982;Strauss 1987;Sedlacek et al 1988;Siemann 1998;Haddad et al 2000). However, several of these studies observed higher abundance of sap-sucking Auchenorryncha and other herbivorous groups, but decreasing evenness and diversity as a small number of species emerged as dominant (Prestidge 1982;Sedlacek et al 1988;Haddad et al 2000).…”
Section: Discussionmentioning
confidence: 99%